Potensi dan Peluang Pengembangan Usaha Produk Kreatif Kulit Ikan Pari Komersial Skala Mikro-Kecil: Potential and Opportunities for Business Development Of Commercial Stingray Leather Products at Micro-Small Scale - Sahubawa, Latif; Sasongko, Heru; Permadi, Ilham; Lutfia, Shila (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Stingray skin can be processed into high value commercial products because it has beautiful pearls on the surface. The research objective was to assess the added value, consumer preferences and the financial feasibility of a commercial stingray leather product business. The research data were analyzed using quantitative and descriptive methods. Added value analysis uses the concept of raw material and final product prices; analysis of consumer preferences using a preference approach with the attributes of the model, price and product color; feasibility analysis using indicators of income, R/C Ratio, PBP and BEP in micro-small businesses Fanri Collection Yogyakarta. Whitespotted whipray and thorn stingray skin products are processed into main products (W/P wallet type 3-in-1 and type 2-in-1) and derivative products (key chains and pearl/beaded bracelets) which are used for value analysis. added. The added value of whitespotted whipray is IDR 920,000 (1,249.9%) and thorn stingray skin is IDR 955,000 (816.7%). Consumers prefer leather products in maroon to bright reds color, browns and moss green and are interested in buying products based on model and price. Fanri Collection’s income is IDR 134,113,500 per year ; value R/C ratio>1.0 (feasible); PBP value for a period of 1 year, 7 months and 7 days; the BEP value is IDR 309,775,383 or sales of 1,936 items per year. The products that consumers are most interested in are key chain and wallet with 3-in-1 type for W/P (woman and man).